Examining the Impact of Transformational Leadership, Digital Innovation, and Sustainable Strategies on Mixue's Business Success in Greater Jakarta Area - Harris Kristanto; Alexander Zebua; Jose Juang Tri Atmojo (Universitas Pelita Harapan, 2024)
This study explores the role of transformational leadership, digital transformation, and innovation in Mixue’s business performance sustainability within Indonesia's competitive food and beverage sector. Since its market entry in 2020, Mixue has grown rapidly by providing affordable, quality products that resonate with young consumers. However, sustaining this growth demands new strategies to address challenges from competitors introducing diverse offerings and digital engagement models. This research finds that transformational leadership fosters adaptability, digital transformation enhances customer engagement and operational efficiency, and continuous innovation secures relevance. Using a quantitative approach with data from Mixue customers, the findings affirm the positive impact of these factors on sustainable business performance. This study highlights the need for an integrated approach to leadership, technology, and innovation for enduring success.